Religion and Animal Welfare—An Islamic Perspective - Rahman, Sira Abdul (Animals (Basel), 2017)
SIMPLE SUMMARY: Cruelty to animals occurs during production, handling, transport, and slaughter in most countries where Islam is a major religion. Most of the people involved in this, such as those involved in the transport of animals, animal handlers, and butchers, are Muslims. However, many Muslims and Islamic religious leaders are not aware of this cruelty. Islam is a religion that shows compassion to animals as mentioned in the holy book Qur’an and sayings of the Prophet Mohammed (pbuh). This paper highlights what Islam says of the welfare of animals and how animal welfare can be improved by sensitizing all Muslims and religious leaders to the teachings on animal welfare in the Qur’an and the Hadiths so that they can influence their followers. ABSTRACT: Islam is a comprehensive religion guiding the lives of its followers through sets of rules governing the personal, social, and public aspects through the verses of the Holy Qur’an and Hadiths, the compilation of the traditions of Prophet Mohammed (pbuh), the two main documents that serve as guidelines. Islam is explicit with regard to using animals for human purposes and there is a rich tradition of the Prophet Mohammad’s (pbuh) concern for animals to be found in the Hadith and Sunna. Islam has also laid down rules for humane slaughter. In many countries animals are killed without pre-stunning. Regardless of pre-stunning, such meat should not be treated as halāl or at least be considered as Makrooh (detestable or abominable), because the animals have been beaten or treated without compassion during production, handling, transport, and slaughter. Many Muslims and Islamic religious leaders are not aware of the cruelty that is routinely inflicted on animals during transport, pre-slaughter, and slaughter in many Islamic countries. There is an urgent need to sensitize all Muslims to the teachings of animal welfare in the Qur’an and the Hadiths. A campaign is needed to apprise religious leaders of the current cruelty that occurs during transport and slaughter.